2021
DOI: 10.1002/smll.202101271
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Pyridinic Nitrogen Sites Promoting Levulinic Acid Hydrogenations over Double‐Shelled Hollow Ru/C Nanoreactors

Abstract: Nitrogen‐doped nanocarbons are widely used as supports for metal‐heterogeneous catalytic conversions. When nitrogen‐doped nanocarbon supports are used to disperse metallic nanoparticles (MNPs), the nitrogen dopant can enhance MNPs electron density to reach higher catalytic activity and promote MNPs stability through anchoring effects. However, the precise identification of active nitrogen species between N‐dopants and reactants is rarely reported. Herein, a proof‐of‐concept study on the active N species for le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Metal–N species [27,30,40,44–47,128] Regulate acid site [28] Change reduction state [35,42] Improve hydrophilicity [28] Increase alkalinity of site [12,23,27,34,45,130] Interaction between metal and N [26,30] Increase the adsorption of substrate [33] Improve metal dispersion [24,25,27,29,31,32,35,36,40,44,45,48] …”
Section: Metal Catalyst Anchored By Heteroatomsmentioning
confidence: 99%
See 3 more Smart Citations
“…Metal–N species [27,30,40,44–47,128] Regulate acid site [28] Change reduction state [35,42] Improve hydrophilicity [28] Increase alkalinity of site [12,23,27,34,45,130] Interaction between metal and N [26,30] Increase the adsorption of substrate [33] Improve metal dispersion [24,25,27,29,31,32,35,36,40,44,45,48] …”
Section: Metal Catalyst Anchored By Heteroatomsmentioning
confidence: 99%
“…The strong metal-sulfur bonding can not only greatly inhibit metal sintering, but also promote the catalytic performance of propane dehydrogenation, phenylacetylene semi hydrogenation and hydrogen evolution reaction (HER). Metal-N species [27,30,40,[44][45][46][47]128] Regulate acid site [28] Change reduction state [35,42] Improve hydrophilicity [28] Increase alkalinity of site [12,23,27,34,45,130] Interaction between metal and N [26,30] Increase the adsorption of substrate [33] Improve metal dispersion [24,25,27,29,31,32,35,36,40,44,45,48] Pyrolysis Similar to N, S doping, B atoms can also be easily incorporated into the carbon skeleton due to its comparable atomic size with carbon. [57,[62][63][64][65][66][67][68] The role of B is basically to form a strong interaction with the metal, thus affecting the electronic and geometric state of the metal (Table 2).…”
Section: Metal Catalysts Anchored By S B and Pmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Zhang et al 180 fabricated atomically precise nitrogen-doped chevron-type graphene nanoribbons by using the on-surface synthesis technique combined with the nitrogen substitution of the precursors. Li et al 30 designed a unique double-shell hollow carbon sphere (DSC) nanoreactor in which ultrafine Ru NPs were encapsulated in a hollow sandwich while precisely modulating pyridine N species by thermal annealing treatment under NH 3 flow on the outer carbon shell only (Figure 33). By precisely identifying the active nitrogen species, it is demonstrated that nitrogen dopants not only improve the catalytic performance of metal NPs but also have an interaction between the nitrogen species and the reactants.…”
Section: ■ Challenges and Perspectivesmentioning
confidence: 99%